Green Nanotechnology Overview and Further Prospects - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2016)
This book, Green Nanotechnology - Overview and Further Prospects, is intended to provide an overview and practical examples of the use of nanomaterials in the new scientific challenges of the green nanotechnology world. We aimed to compile information from a diversity of sources into a single volume to give some real examples, extending the concept that green nanotechnology is far from being a scientific conundrum, and instead a real answer to some of the actual problems the whole planet is dealing with.